Production of Sorbitol from Meranti Wood Sawdust (MWS) using Immobilized Cells via Solid State Fermentation (SSF) Process:OFAT Study - Zuriana, Sidi Ahmad; Mimi Sakinah, A. M.; Farhan, Mohd Said (Universiti Malaysia Pahang, 2016)
Malaysia is the largest country that has produced many types of waste. One of it is Meranti wood sawdust (MWS). These wastes result in a significant environmental problem if not dispose of in the proper manner. The Agroindustrial like MWS has great potential as a substrate for sorbitol fermentation and others biochemical products. The objective of this study is to produce the high production of sorbitol via solid state fermentation (SSF) process from treated MWS using immobilization cells of bacteria (Lactobacillus plantarum sp. strain BAA 793) by entrapment technique (entrapped in sodium alginate). Besides that, one factor at a time (OFAT) were study for further process by solid state fermentation (SSF) process using immobilized cells and investigated the effect of relevant parameters (fermentation time, range: 2hours to 8hours, moisture content, range: 40% to 80%, substrate amount, range: 0.5gram to 2.5gram) to the solid-state fermentation (SSF) process in producing high yield of sorbitol production. The optimum fermentation time is at 4 hours after fixing the substrate amount at 2 g and moisture content at 50 % and the sorbitol production was about 8.396 g/L. Then, 50 % of moisture content will give optimum production of sorbitol, whereby the product was about 4.726 g/L after fixing the substrate amount at 2 g and fermentation time at 6 hours. The production of sorbitol is optimum at 1.0 g of substrate where is the production of sorbitol is about 12.210 g/L after fermentation time was maintained at 50% and 4 hours The highest product was obtained at 50% moisture content, at 4 hours of fermentation time and 1.0 gram of substrate amount whereby the concentrations of sorbitol was 12.21 g/L respectively. These results also indicate that the solid state fermentation (SSF) process will produce the high yield of sorbitol production using immobilized cells with control the important parameter.